The Determinants of Graduate Students on Satisfaction: The Case of Graduate School at University of Internal Affairs, Mongolia - Sarantsetseg, Bazarvaani; Baigalmaa, Sosorbaram; Odmaa, Natsagdorj; Gunchinlham, Enkhtuya (Advances in Social Sciences Research Journal, 2024)
The present article aims to study the level of satisfaction of the graduate students’ satisfaction on Graduate school in University Internal Affairs, Mongolia /UIAM/. We try and understand the factors which influence graduate student satisfaction in higher education, as well as the consequences of it. We collected and analyzed data from descriptive research can help understand factors on graduate students’ satisfaction. The data were collected from 98 graduate students who study graduate school of the curriculum on Disaster Studies, Border Studies, Law, Crime Studies Law, Police Studies, Forensic science, Information Security, and Economic Security in UIAM. The results, there were indicated positive graduate students' satisfaction of the hypothesis 1 and hypothesis 2. Actually, the results indicated the dissatisfaction of the hypothesis-3. Therefore, it is recommended that the curriculum activities take the necessary measures in order to increase the students’ satisfaction and the level of training activities. Our study is significant in considering both theoretical and practical issues and for practices in graduate school. Data were estimated by Smart PLS 3.0 and SPSS software and Cronbach's alpha index have been used for data analysis and reliability analysis of the questionnaire, respectively.